Chapter of Wisdom of Malikiyyah about the Concept of Loatiyyah - Hamid Parsania (حکمت اسرا, 2011)
The focus of this paper is to explore a few important mystical points in the Chapter of Wisdom of Malikiyyah in Fusus al-Hikam which deals with the concept of Lutiyyah. The chapter of Luti in Fusus al-Hikam consists of a wisdom revealed to the Prophet Loath (as). This wisdom was the result of his intense longing for God referred to in the Qur’an. Dawud al-Qaysari introduces the main four topics which are examined in this chapter: 1- weakness of existence in human beings and other creatures is inherited in their essence. 2. Being perfect knowledge as obstacle for mystic’s free activities 3. Revealing the secrets of Divine Determination Another important issue in this chapter is natural genetic contradiction in natural things on the one hand and intellectual contradiction among believers and unbelievers on the other. Here, the author of the book explains the concept of Unity and how multiplicity is the cause of all contradictions in the physical world.